Optimization of Processed Fish Management in Prigi Tourism Area Through Packaging Strategies and Product Diversification - Angga Rizka Lidiawan; Sudjiono; Alma Hariyati; Risma Gesang Ayu Cahyani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Fish contains high nutrients that can be consumed by most humans. Fish also has nutritional content in animal and vegetable proteins that are low in cholesterol so it is safe for consumption. The availability of abundant fish but not balanced with good management makes public consumption interest in fish less able to maximize the availability of abundant raw materials, there is no diversification of processed products, packaging used by partners to wrap products is less attractive, and less able to maximize the development of technology and information is the main focus of problems in this service. The method in this service is Focus Group Discussion with several stages. As a result of this dedication, partners can diversify products and do online marketing.